A National Idea in Conditions of the Islamic Revival - G. E. Nadirova; Sh. S. Kaliyeva; A. A. Mustafaeva; B. Zh. Aktaulova (Zenodo, 2012)
Discussion and development of principles of the uniform nation formation within the limits of the Kazakhstan state obviously became one of the most pressing questions of the day. The fact that this question has not been solved "from above" as many other questions has caused really brisk discussion, shows us increase of civil consciousness in Kazakhstan society, and also the actuality of this theme which can be carried in the category of fatal questions. In any sense, nation building has raised civil society to a much higher level. It would be better to begin with certain definitions. First is the word "nation". The second is the "state". Both of these terms are very closely connected with each other, so that in English language they are in general synonyms. In Russian more shades of these terms exist. For example in Kazakhstan the citizens of the country irrespective of nationality (but mainly with reference to non-kazakhs) are called «kazakhstanians», while the name of the title nation is \"Kazakhs\". The same we can see in Russia, where, for example, the Chechen or the Yakut –are \"Rossiyane\" which means "the citizens of Russian Federation, but not \"Russians\". The paper was written under the research project "Islam in modern Kazakhstan: the nature and outcome of the religious revival".